Impact of vaccination and treatment on SIRS model with Non-linear incidence rate - Arkan N. Mustafa; Hanaa J. Ahmed (Tikrit Journal of Pure Science)
In this paper, an epidemic model consisting of susceptible, vaccination, infected and removal is formulated mathematically. The proposed model deals with incorporating the vaccination factor, treatment factor and non-linear incidence rate. Non negative for the model Solutions are proved, a simplex attractor invariant set is found, the basic reproduction number of the model is calculated using the method of the next-generation matrix, and the model equilibrium points performed a local stability analysis, we have collected the infected cases COVID-19 real data in Kurdistan region from Iraq to estimate the model parameters and sensitivity of the basic reproduction number and the model variable to the parameters of the model was studied